Combination of Biological and Inorganic Fertilizer on Growth and Production of Rice (Oryza Sativa): Mini Review - Lidong, Andini (Science Tech Group, 2024)
Rice production in Indonesia fluctuates annually, often due to limited nutrient availability for optimal plant growth. A promising approach to enhance rice productivity and sustainability is the combination of biological and inorganic fertilizers. This review examines the effects of combined fertilization on lowland rice growth and yield, evaluating different fertilization strategies. Treatments included no fertilization, standard inorganic fertilization, and varied combinations of biological and inorganic fertilizers. Findings reveal that specific combinations improved rice growth parameters such as plant height, tiller number, and leaf color intensity, achieving similar or superior results compared to inorganic fertilizers alone. Moreover, this integrated approach demonstrated enhanced productive tiller counts and grain yield, indicating higher agronomic efficiency. These insights underscore the potential benefits of using combined fertilization strategies to optimize rice productivity while promoting sustainable agricultural practices.